Acceptability and Preliminary Effects of Intensive Brief Trauma-Focused PTSD Treatment for Refugees - Petter Tinghög; Lina Vågbratt; Julia Jennstål; Maria Bragesjö; Niklas Möller (Torture)
Background: Post-Traumatic Stress Disorder (PTSD) is a significant mental health concern in refugee populations exposed to trauma and displacement. Traditional treatments for PTSD often involve lengthy interventions. However, there's a growing interest in exploring more condensed, intensive treatments to improve outcomes and accessibility for refugees. Objective: This study aimed to evaluate the acceptability, and preliminary effects of an intensive brief trauma-focused PTSD treatment (ITT) program delivered to refugees at the Swedish Red Cross Treatment Center for Persons Affected by War and Torture in Uppsala, Sweden. Method: Ten participants were enrolled in the study and received ITT over five consecutive weekdays comprising Eye Movement Desensitization and Reprocessing Therapy (EMDR), prolonged exposure (PE), and physical activity (PA). Acceptability was assessed by analyzing journal notes, and clinicians’ and patients’ open-ended responses to sets of questions designed to elicit the patients’ experiences and potential adverse events. Baseline and follow-up data regarding PTSD (i.e., PCL-5 and CAPS-5), disability (i.e., Whodas-12), and anxiety or depression (i.e., HSCL-25) were collected and analyzed. Results: The study demonstrated that ITT is an acceptable and viable treatment option for refugees with PTSD. No serious adverse events were reported, although some found the treatment very taxing. Overall, the ordeals were perceived as worthwhile. The statistical analyses showed substantial and significantly reduced PTSD symptoms, and anxiety levels i.e., CAPS-5 (Cohen’s d 1,91; CI 95% 0.77-3.02), PCL-5 (Cohen’s d 1,31; CI 95% 0.43 -2.15) Anxiety subscale of HSCL-25 (Cohen’s d 1.47; CI 95% 0.49 -2.41). Reductions in depression symptoms and disability were also observed but were non-significant. Conclusions: The results suggest that this brief and massed treatment program for refugees with PTSD is a well-received and preliminary effective treatment option. Identifying less suitable candidates and conducting larger, controlled studies with longer follow-up periods are needed to establish ITT's efficacy in this population.